Genetic enhancement of oil content in potato tuber (Solanum tuberosum L.) through an integrated metabolic engineering strategy. Issue 1 (11th July 2016) - Liu, Qing; Guo, Qigao; Akbar, Sehrish; Zhi, Yao; El Tahchy, Anna; Mitchell, Madeline; Li, Zhongyi; Shrestha, Pushkar; Vanhercke, Thomas; Ral, Jean‐Philippe; Liang, Guolu; Wang, Ming‐Bo; et al.
Summary: Potato tuber is a high yielding food crop known for its high levels of starch accumulation but only negligible levels of triacylglycerol (TAG). In this study, we evaluated the potential for lipid production in potato tubers by simultaneously introducing three transgenes, including WRINKLED 1 ( WRI1 ), DIACYLGLYCEROL ACYLTRANSFERASE 1 ( DGAT1 ) and OLEOSIN under the transcriptional control of tuber‐specific (patatin) and constitutive (CaMV‐35S) promoters. This coordinated metabolic engineering approach resulted in over a 100‐fold increase in TAG accumulation to levels up to 3.3% of tuber dry weight (DW). Phospholipids and galactolipids were also found to be significantly increased in the potato tuber. The increase of lipids in these transgenic tubers was accompanied by a significant reduction in starch content and an increase in soluble sugars. Microscopic examination revealed that starch granules in the transgenic tubers had more irregular shapes and surface indentations when compared with the relatively smooth surfaces of wild‐type starch granules. Ultrastructural examination of lipid droplets showed their close proximity to endoplasmic reticulum and mitochondria, which may indicate a dynamic interaction with these organelles during the processes of lipid biosynthesis and turnover. Increases in lipid levels were also observed in the transgenic potato leaves, likely due to the constitutive expression of DGAT1 and incomplete tuber specificity of the patatin promoter. This study represents an important proof‐of‐concept demonstration of oil increase in tubers and provides a model system to further study carbon reallocation during development of nonphotosynthetic underground storage organs.